Effects of broadband availability on total factor productivity in service sector firms: Evidence from Ireland. (February 2019) - Haller, Stefanie A.; Lyons, Sean
Abstract: While broadband is widely believed to augment productivity, there is little firm-level evidence of a generalised causal effect. In this paper we examine whether the introduction of digital subscriber line (DSL) broadband services increased firms' productivity in nine sub-sectors within the services and distribution sector in Ireland from 2006 to 2012. Firm-level panel data on firms' characteristics are linked to spatial information on the rollout of DSL. While we do not find significant productivity effects in the services sectors taken together, we do find positive and significant effects on firm's total factor productivity in Information & Communication and Administrative & Support Services. Highlights: Examines whether introduction of DSL broadband increased productivity in services. Data on service firms in Ireland linked to spatial data on broadband rollout. No significant productivity effects found in services as a whole. Significant increase in Total Factor Productivity for 2 out of 9 service sectors.